STUDY ON INDUCTION OF EMBRYOGENETIC CALLUS AND PLANT REGENERATION CAPACITY FROM IMMATURE EMBRYOS OF VIETNAM MAIZE LINES - Đồng, Nguyễn Văn (Vietnam Journal of Biotechnology, 2011)
Maize (Zea mays L.) is one of the world three most widely cultivated crops. Many maize transgenic lines were developed by application of transformation technology. However, the transformation researches were limited due to almost edible lines showed poor regeneration response. We have evaluated different formulations for callus induction of 46 maize lines include flint com, waxy com, sweet com and one model line (HR8) have proven to be responsive to the in vitro conditions considered in this work. The results revealed 6 flint com Hnes (VHl, VHll, VH19, VH29), 3 waxy com lines (VHN9, VHNIO, VHN16) and 2 sweet com lines (VHD2, VHD5) showing the high efficiency in embryogenic callus formation and good agricultural characters. The medium supplemented sucrose (20 g/l) and glucose (10 g/l) combining with BAP 0.3 mg/l and 2.4-D 1.5 mg/l significantly improved the frequency of embryogenic callus induction of these lines, especially VDHl sweet com line. This was the first report which has defined the selected maize lines of Vietnam giving high regeneration ability. They will be used as meterial sources for maize transformation research, producing genetically modified lines adapted with Vietnam's weather, reducing the time for breeding.